Business Plan : Gorgeous Coffees / Aziza Shamsudin ... [et al.] - Shamsudin, Aziza; Yasin, Wandiana Mariyam; Othman, Noor Izzaty; Noor Muhammad, Nurul Umairah; Ramli, Nurul Afifah (2009)
Business plan is important because it explains about all the activities, strategy, financial and other that are related to the business. People and entrepreneurship will easy to construct new business from business plan because it has a lot of information about the business. The business plan will explain in details about our partnership business product and service which is coffee. The product name is Coffee which is produced by our company Gorgeous Coffee. As a service company, we are aiming to become the best company in Malaysia. Besides that, we aim to become the leading ‘Bumiputra’ business in giving services. Because most of ‘non-Bumiputra’ company conquering this business, we want to exist the immolate culture among competitors. Our other aim in this business world is to capture the market share and provide a good product and service in local market and able to satisfy our customer’s needs. By introducing our company to the public in the short period of time; we would like to improve our performance along the years.